Translation errors among bilingual Arabic language students: collocations as an example - Ahmad, Aliyu; Mustapha, Nik; Syed Abdullah, Syed Nurulakla; Toklubok, Pabiyah (King Faisal University, 2023)
The study of translation by bilingual female students studying Arabic had not received much attention, especially with regard to the cultural errors that these students made during English-Arabic translations, which resulted in them making mistakes in translation. This prompted the researchers to focus on this area. The main objective of this article is to explore common errors in English-Arabic collocation translation among Arabic students in the Federal College of Education (Technical), Gusau and identify possible reasons for them. The researchers used a qualitative analysis approach, adopting an evaluation instrument. A semi-structured interview was also conducted among the sample group in order to find out the causes of the errors. The results showed that the students encountered errors in translation collocations, which included lexical and grammatical collocations. Reasons for these errors included: a lack of collocations knowledge, a lack of special books and dictionaries of collocations and an inability to identify an equivalent to English collocations in the Arabic language. This study is extremely important for students of Arabic, scholars, and English-Arabic translators, as it alerts them to common errors in English-Arabic translation.